Horizontal buoyant jets into viscoplastic ambient fluids - M.H. Moosavi; H. Hassanzadeh; S.M. Taghavi (Applications in Engineering Science)
This study investigates the horizontal injection of a heavy Newtonian fluid into a lighter viscoplastic ambient fluid, in a large reservoir. The flow dynamics is experimentally captured via camera imaging, laser-induced fluorescence, and particle image velocimetry techniques. The flow parameters include various density differences, injection velocities, and ambient fluid viscoplastic properties. Our analysis identifies two key dimensionless numbers, the Froude number (Fr) and the effective viscosity ratio (m), which includes the rheology of the viscoplastic fluid. Our study also examines the effects of these dimensionless numbers on critical jet characteristics, such as bifurcation length, transition length, deviation length, and jet trajectory, and provides correlations using Fr and m, to predict these characteristic lengths. A regime classification based on the bifurcation phenomenon is also presented in the Fr−m plane.